Validity and reliability of the Polish version of the Pregnancy Mobility Index (PMI-PL) - Antosiak-Cyrak, Katarzyna; Ratajczak, Joanna; Lewandowska, Magdalena; Wochna, Krystian; Sobczak, Katarzyna; Domaszewska, Katarzyna; Rąglewska, Patrycja; Urbański, Piotr; Czerniak, Urszula; Demuth, Anna (Frontiers in Public Health, 2024)
Mobility, defined as active, controlled, multi-joint flexibility used in movement, is limited in pregnant women due to problems with low back pain (LBP) and pelvic girdle pain (PGP). The Pregnancy Mobility Index (PMI) is a tool for assessing mobility in relation to LBP/PGP. The lack of a Polish version of the PMI test prompted a transcultural adaptation to the Polish conditions. The aim of the study was to evaluate the measurement properties of the Polish adaptation of the Pregnancy Mobility Index. The study involved 121 pregnant women aged 18-44. The translation process was in accordance with the Beaton et al. (2000) transcultural adaptation design. Reliability was assessed by intraclass correlation coefficient (ICC). Construct validity between the Polish version of the PMI (PMI-PL) and the Physical Activity Pregnancy Questionnaire (PPAQ-PL) was assessed by Spearman's rank correlation coefficient. The transcultural adaptation of the PMI test into Polish was satisfactory, with high internal consistency (Cronbach's alpha = 0.97-0.98, ICC = 0.989). Statistically significant inverse proportional correlations were found for total PA, total PA (light and above), light PA, moderate PA, and vigorous PA in the construct validity analysis between PMI-PL and PPAQ-PL. The Polish version of the PMI is a reliable instrument. The introduction of a questionnaire with a classification system will make it easier for health professionals to monitor the health status of pregnant women and encourage them to engage in physical activity appropriate for their current level of mobility.